(untitled) (Applied Biological Research, 2014)
Citrus canker caused by Xanthomonas citri subsp. citri is one of the most important disease of citrus in India. In the present study 23 isolates of Xanthomonas citri subsp. citri were collected from Varanasi and Jaunpur districts of Uttar Pradesh (India). Isolates showed similar biochemical characteristics whereas molecular analysis involving repetitive polymerase chain reaction [rep-PCR] (BOX-, ERIC- and REP-PCR) grouped these isolates into six clusters at 50% similarity coefficient, thereby revealing presence of variation in X. citri subsp. citri isolates.